(untitled) (CIPEEX, 2025)
This study presents a literature review on the use of artificial intelligence (AI) in academic work and its implications for teaching and learning processes, particularly within the Human and Social Sciences. The objective is to analyze how AI, while representing an innovative and valuable tool, also poses pedagogical and ethical challenges, especially in the training of psychologists. The method consisted of a review of recent publications addressing both the benefits and the risks associated with the indiscriminate use of AI in academia. The results show that AI can significantly contribute to academic production and pedagogical development by supporting research and expanding access to information. However, concerns arise regarding the superficiality of learning processes, the potential compromise of intellectual autonomy, and the risk of replacing critical reflection with automated responses. Furthermore, the findings highlight the need for both faculty and student training to ensure conscious and qualified use of this technology. It is concluded that, although AI is a promising ally in education, its adoption requires a critical stance, ethical regulation, and pedagogical practices that safeguard academic integrity and the quality of Psychology education.